Metal Oxide Semiconductor Gas Sensors for Lung Cancer Diagnosis - Li, Guangyao; Zhu, Xitong; Liu, Junlong; Li, Shuyang; Liu, Xiaolong (Chemosensors, 2023)
Lung cancer is the most prevalent severe illness in both sexes and all ages and the leading cause of cancer-related deaths globally. Late-stage diagnosis is the primary cause of its high mortality rate. Therefore, the management of lung cancer needs early-stage screening. Breath analysis is a non-invasive, low-cost, and user-friendly approach to diagnosing lung cancer. Among the various types of breath sensors, MOS gas sensors are preferred due to their high gas responses, fast response times, robustness, and lower price. This review focuses on the critical role of MOS gas sensors in detecting VOCs in lung cancer patients’ exhaled breath. It introduces the basic working mechanism of MOS gas-sensitive materials, summarizes some high-performance MOS materials suitable for detecting potential lung cancer biomarkers and provides performance enhancement strategies. The review also briefly introduces the sensor array and its pattern recognition algorithm. Finally, we discuss the challenges in developing MOS gas sensors for lung cancer screening and present the prospect of using the e-nose for large-scale early lung cancer screening.